PENGARUH KEPUASAN, KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS PELANGGAN ( Studi Kartu Perdana XL pada Mahasiswa Universitas Stikubank Semarang ) - Yusuf Rifki Mahardika, 08.05.51.0057; Kasmari, Kasmari (Students Journal of Economic and Management, 2012)
The purpose of this study was to determine the effect of satisfaction, trust and commitment to customer loyalty. Based on the research goal is to take title